2016
DOI: 10.1016/j.jgeb.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Aceh cattle breed of Indonesia through mitochondrial D-Loop region

Abstract: The objective of this research was to find the basic data on genetic diversity of mtDNA D-Loop in Aceh cattle and its association with Bhutanese, Chinese, and Indian cattle. There were sixty samples of DNA which had been sequenced; i.e. Banda Aceh (11), Saree (20), and Indrapuri (29). To the best of our knowledge this is the first published data on the complete mitochondrial D-Loop sequence of Aceh cattle. Results show that Aceh cattle have the closest relationship to Bos indicus and have been influenced by Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…Interestingly, with a few samples observed in this study, we also detected specific haplotypes including Hap_17 (in Pasundan cattle), Hap_18 and Hap_19 (in Pacitan cattle), with only one individual of each haplotype (Table 2). Specific haplotypes were also found in Aceh cattle inferred from D-loop sequences (Sari et al 2016). In addition, Adinata et al (2017)…”
Section: B I O D I V E R S It a Smentioning
confidence: 84%
“…Interestingly, with a few samples observed in this study, we also detected specific haplotypes including Hap_17 (in Pasundan cattle), Hap_18 and Hap_19 (in Pacitan cattle), with only one individual of each haplotype (Table 2). Specific haplotypes were also found in Aceh cattle inferred from D-loop sequences (Sari et al 2016). In addition, Adinata et al (2017)…”
Section: B I O D I V E R S It a Smentioning
confidence: 84%
“…Currently, D-loop mitochondrial based on partial sequencing for investigation of genetic diversity was reported in some cattle breeds such as Aceh cattle (Sari et al, 2016), Bali cattle and Madura cattle (Nijman et al, 2003). Besides, the D-loop mitochondrial analysis was also carried out in Bali cattle, Madura cattle, PO cattle, and Pesisir Sumatra Barat cattle (Sutarno, 2010) as well as SO cattle (Agung and Hermansyah, 2018) using polymerase chain reaction-fragment length polymorphism (PCR-RFLP).…”
Section: For This Reason D-loop Mitochondrial Is Oftenmentioning
confidence: 99%
“…Previously, the clustering of cattle breeds based on genetic distance and the genetic tree was commonly performed using Bos taurus and Bos inducus (Chung, 2013;Xuan et al, 2010), since reference related to Bali cattle as Bos javanicus cluster has been scarcely available. Genetic diversity of cattle breeds could be researched not only according to partial fragment of D-loop mtDNA (Correia et al, 2017;Sari et al, 2016), complete fragment of dloop mtDNA (Lorenzo et al, 2018), but also whole sequence of mtDNA genome (Pramod et al, 2018). Yet, it is noteworthy that the results of the analysis using entire fragments are expected to collect comprehensive relationships between individuals within species or among species closely related with divergence time (Rehman et al, 2017).…”
Section: Genetic Distance and Genetic Tree In Bali Cattle And So Cattlementioning
confidence: 99%
“…Until recently, research on Simeulue buffalo which concerned in genetic studies has only been carried out by Sari (2014). The study revealed that Simeulue buffalo had a close relationship with Riau buffalo and they situated in a separate cluster from Aceh buffalo in Central Aceh and Aceh Besar.…”
Section: Introductionmentioning
confidence: 98%